Caught between Cultures: Unintended Consequences of Improving Opportunity for Immigrant Girls - Gordon B. Dahl; Christina Felfe; Paul Frijters; Helmut Rainer (Center for Economic Studies and ifo Institute (CESifo), 2020)
What happens when immigrant girls are given increased opportunities to integrate into the workplace and society, but their parents value more traditional cultural outcomes? Building on Akerlof and Kranton's identity framework (2000), we construct a simple theoretical model which shows how expanding opportunities for immigrant girls can have the unintended consequence of reducing their well-being, since identity-concerned parents will constrain their daughter's choices. The model can explain the otherwise puzzling findings from a reform which granted automatic birthright citizenship to eligible immigrant children born in Germany after January 1, 2000. Using survey data we collected in 57 German schools and comparing those born in the months before versus after the reform, we find that birthright citizenship lowers measures of life satisfaction and self-esteem for immigrant girls. This is especially true for Muslims, where traditional cultural identity is particularly salient. Birthright citizenship results in disillusionment where immigrant Muslim girls believe their chances of achieving their educational goals are lower and the perceived odds of having to forgo a career for family rise. Consistent with the model, immigrant Muslim parents invest less in their daughters' schooling and have a lower probability of speaking German with their daughters if they are born after the reform. We further find that immigrant Muslim girls granted birthright citizenship are less likely to self-identify as German and are more socially isolated. In contrast, immigrant boys experience, if anything, an improvement in well-being and other outcomes we examine. Taken together, the findings point towards immigrant girls being pushed by parents to conform to a role within traditional culture, whereas boys are allowed to take advantage of the opportunities that come with citizenship. Alternative models can explain some of the findings in isolation, but are not consistent more generally.
Keywords: Z10; J15; J16; 330; identity; citizenship; immigration; integration